A pilot study on gene expression of endoplasmic reticulum unfolded protein response in chronic kidney disease - Mostafa, Rasha G. (Biochem Biophys Rep, 2020)
BACKGROUND: Chronic kidney disease (CKD) is a worldwide public health problem due to its increasing prevalence worldwide. Endoplasmic reticulum (ER) stress has been shown to play a role in the pathogenesis of various renal diseases in humans. It leads to the activation of the unfolded protein response (UPR) which triggers three known trans membrane sensors in the ER: activating transcription factor 6 (ATF6), inositol-requiring enzyme I (IRE1), and PKR (double-stranded RNA-dependent protein kinase)-like ER protein kinase (PERK). The activation of these signal transduction pathways can result in cell death, inflammation, and fibrosis in the context of CKD. OBJECTIVES: The aim of this study was to detect the level of gene expression of activating transcription factor 6 (ATF6), inositol-requiring enzyme I (IRE1), and PKR (double-stranded RNA-dependent protein kinase)-like ER protein kinase (PERK) in chronic kidney disease patients. SUBJECTS AND METHODS: This study was carried out on eighty subjects, 50 patients with CKD (25 with hypertension and 25 without hypertension) and 30 healthy subjects served as controls. All studied subjects underwent laboratory investigations, including CBC, Serum Lipid profile: Total cholesterol, Triglycerides, HDL-cholesterol and LDL-cholesterol, liver and kidney functions, fasting and 2 h postprandial blood glucose and HbA1C, serum level of IL6 and gene expression of ATF6, IRE1 and PERK using real time PCR technique. RESULTS: There was a significant increase in relative quantitation (RQ) of gene expression of IRE1, ATF6 and PERK in chronic kidney patient groups with hypertension and without hypertension compared to control group. Also, there was a significant positive correlation of PERK and ATF6 gene expressions and a significant negative correlation of PERK gene expressions and GFR in groups I&II. CONCLUSION: Endoplasmic reticulum (ER) stress occurs in CKD with activation of gene expression of three trans-membrane sensors in the ER: activating transcription factor 6 (ATF6), inositol-requiring enzyme I (IRE1), and PKR (double-stranded RNA-dependent protein kinase)-like ER protein kinase (PERK).